Dose rates and specific activities of copper based materials irradiated during the TT plasma operation at JET. (January 2020) - Tidikas, Andrius; Breidokaite, Simona; Slavickas, Andrius; Stankunas, Gediminas; ,
Highlights: For the safe ITER operations it is necessary to evaluate high thermal conductivity materials which should be interposed between the armour and the cooling channels. For these calculations two types of alloys were selected: CuCrZr, Al-Bronze. Cu-64 and Ni-63 were identified as most important radionuclides in terms of activity for both CuCrZr and Al-Bronze after the end of irradiation and after 1 year of cooling respectively. Cu-64 was identified as most important radionuclides in terms of dose rate for both CuCrZr and Al-Bronze. Both Co-60 and Co-58 contributed to the total dose rate the most after 1 year of cooling for CuCrZr and Al-Bronze respectively. 1 year after the end of irradiation, specific activities for Al-Bronze and CuCrZr samples are 0.68 MBq/kg and 0.35 MBg/kg respectively and can be considered to be low level radioactive waste. Abstract: Before deuterium-tritium (DTE2), a new tritium campaign (TT) with the objective to validate the activities, dose rates for selected materials and OLTIS container components, as resulting from neutron irradiation at Joint European Torus (JET), is planned. This paper describes the activation and dose rate calculation performed for copper based materials irradiated throughout the foreseen TT plasma operation. Preparatory experiments and calculations are in progress for TT campaign to measure neutron flux spectrum at the irradiation position using dosimetry foils. In addition, the materials to be considered for irradiation during the TT campaign of the OLTIS were identified and analyzed in this study: Al-Bronze and CuCrZr. The neutron-induced activities and dose rates at shutdown were calculated by activation inventory code FISPACT-2010 using the neutron fluxes and spectra provided by the detailed MCNP5 neutron transport calculations. After the irradiation, the activities and dose rates are calculated at several cooling times after the end of irradiation. Highest dose rates the end of irradiation are attributed to Cu-64 radionuclide. Co-58 and Co-60 are the most dominant radionuclides during intermediate and long cooling periods. Highest activities are ascribed to Cu-64 at the beginning and Ni-63 at the end of investigation time.